Utilization of animals in the manyarung ritual ceremony at banuaka' taman kapuas, sayut village - Ege, Benediktus; Supiandi, Markus Iyus; Bustami, Yakobus; Julung, Hendrikus; Utami, Yuniarti Essi (STKIP Persada Khatulistiwa Sintang, 2025)
The Banuaka' Taman Kapuas community in Sayut Village, South Putusibau District, Kapuas Hulu Regency, West Kalimantan Province has traditional knowledge about the use of animals in the Manyarung ritual ceremony that has never been documented in writing. This study aims to document the types of animals, the parts of the animals used, the methods of utilization, and the symbolic meanings of the animals in the Manyarung ceremony within the Banuaka’ Taman Kapuas community. The research employs a descriptive qualitative method using survey techniques. Data collection tools consist of interview sheets, and data analysis is conducted using a qualitative approach. The results of this study are that there are 11 species of animals used in the Manyarung ceremony. All parts of the animal's body are used in the ritual. Methods of use include boiling, grilling, frying, fermenting, and cutting into several pieces in a fresh/raw condition. The symbolic meaning of 7 animals as food that should not be eaten (taboo) by the balien (shaman) during the period of treating the sick, and 4 animals have the meaning of a means to summon the spirits of the ancestors so that they can come to the ceremony.